Implementation of Artificial Intelligence based on Natural Language Processing to Enhance MSME Sales - Alawiah, Enok Tuti; Setyorini, Dini; Apriyani, Helina (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
Micro, small and medium enterprises have contributed to gross domestic product and help support the people's economy. However, there are many challenges in the era of digital transformation so that MSMEs must innovate so that their products can be accepted by the market more widely. This study aims to help MSMEs increase their sales by carrying out digital transformation through a website-based sales information system equipped with a chatboot facility based on natural language processing. The goal is to provide a different experience for customers in shopping online and convenience for MSMEs in providing customer service satisfaction. The implementation of artificial intelligence based on natural language processing is expected to help micro, small and medium enterprises in expanding the market, increasing sales and providing a different experience in shopping.